Non-traditional regular purchasing arrangements in public procurement: a doctrinal and comparative analysis of regulation and implementation systems - Filipon, Liviu Serban (2018)
This research analyses, by using legal doctrinal and comparative methods, non-traditional regular purchasing arrangements (NTRPA) in seven public procurement systems carefully selected to ensure a wide coverage: the UNCITRAL Model Law on Public Procurement (2011), the World Bank, the US federal procurement system, the EU system and three EU Member States: UK, Romania and France.